Enhanced Photocatalytic Performances and Mechanistic Insights for Novel Ag-Bridged Dual Z-Scheme AgI/Ag3PO4/WO3 Composites - Chunlei Ma; Jianke Tang; Qi Wang; Rongqian Meng; Qiaoling Li (Inorganics, 2025)
In this study, AgI/Ag3PO4/WO3 ternary composite photocatalysts with dual Z-scheme heterojunction were fabricated via the in situ loading of Ag3PO4 onto WO3 followed by anion exchange. Compared to single photocatalysts and binary composites, the AgI/Ag3PO4/WO3 composites exhibited enhanced photocatalytic activity in the photodegradation of chlortetracycline hydrochloride (CTC) under visible-light irradiation. Notably, the AAW-40 photocatalyst, which contained an AgI/Ag3PO4 molar ratio of 40%, degraded 75.7% of the CTC within 75 min. Moreover, AAW-40 demonstrated an excellent performance in the cyclic degradation of CTC over four cyclic degradation experiments. The separation and transfer kinetics of the AgI/Ag3PO4/WO3 composite were investigated with photoluminescence spectroscopy, time-resolved photoluminescence spectroscopy, and electrochemical measurements. The improved photocatalytic performance was primarily due to the creation of a silver-bridged dual Z-scheme heterojunction, which facilitated the efficient separation of photoinduced electron–hole pairs, retained the strong reducing capability of electrons in AgI, and ensured the strongly oxidizing nature of the photoexcited holes in WO3. The dual Z-scheme charge-transfer mechanism was further validated using in situ X-ray photoelectron spectroscopy. This study provides a foundation for developing innovative dual Z-scheme photocatalytic systems aimed at the efficient degradation of antibiotics in wastewater.